MUSIC IN BUDDHISM: RELIGIOUS AND SPIRITUAL SIGNIFICANCE - Singh, Sangram; Aneja, Richa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper discusses the religious significance and use of music in Buddhism and Jainism. The purpose of music in Buddhism is to stabilize the mind of the practitioner and deepen the process of meditation. The recitation of Buddhist scriptures, chanting of mantras and the use of musical instruments like bells, damaru and conch in the Tibetan Buddhist tradition make meditation effective. Buddhist music helps in increasing concentration and mental peace of the practitioner through Pali and Sanskrit hymns and Tibetan mantras. The singing of the Tibetan mantra "Om Mani Padme Hum" helps in achieving inner balance and peace. The use of music in Jainism is important in the purification of the soul and the process of meditation. The singing of Jain devotional songs, such as the "Bhaktamar Stotra", inspires seekers to asceticism and self-reliance. Jain music includes the singing of Samayik and Pratikraman songs towards atonement of sins and purification. The use of musical instruments, such as the veena, mridanga, harmonium, and tabla, convey religious fervour and peace.